Compound non-starch polysaccharide enzymes improve growth performance, slaughter performance, immune function, and apparent utilization rate of nutrients in broiler chickens fed a low-metabolizable energy diet - Chen, Xing; Zhang, Guang-min; Wang, Wei-wei; Liu, Guo-hua; Cai, Hui-yi; Purba, Adanan; Zheng, Ai-juan (Frontiers in Veterinary Science, 2023)
This study aimed to investigate the effects of compound non-starch polysaccharide (NSP) enzymes on growth performance, slaughter performance, immune function, and apparent utilization of nutrients in broiler chickens fed a low-metabolizable energy diet. A total of 240 healthy 1-day-old AA broilers (Arbor Acres, 47.2 ± 0.31 g) were randomly divided into four treatment groups, each with six replicate groups and 10 broilers per replicate. The control group was fed a basal diet; the EL-H group was fed the basal diet supplemented with 200 mg/kg compound NSP enzyme, including β-mannanase 5,000 IU/g, β-glucanase 2000 IU/g, xylanase 10,000 IU/g, and cellulase 500 IU/g. The EL-M group was fed the basal diet with 50 kcal/kg metabolizable energy removed, supplemented with 200 mg/kg compound NSP enzyme. Finally, the EL-L group was fed the basal diet with 100 kcal/kg metabolizable energy removed, supplemented with 200 mg/kg compound NSP enzyme. The results showed that feeding with a low-metabolizable energy diet supplemented with compound NSP enzymes did not significantly affect the growth performance of broilers (p > 0.05). Compared with the control group, the abdominal fat rate of broilers in the EL-L group was significantly reduced, and that of broilers in the EL-M group was significantly increased (p < 0.05). Apparent utilization of dry matter, crude protein, and energy in the diet was lower in the control group than in the EL-L group, but significantly higher in the control group than in the EL-H group (p < 0.05). In addition, apparent utilization of crude fiber was significantly increased in the EL-H, EL-M, and EL-L groups compared with the control group (p < 0.05). In conclusion, this experiment showed that the addition of 200 mg/kg compound NSP enzyme enabled maintenance of the normal growth and development of broiler chickens fed a low-metabolizable energy diet (replacing 50–100 kcal/kg metabolizable energy). This study provides a theoretical basis for the application of the compound NSP enzyme in broiler chickens.